INTRAKSI SOSIAL DALAM KELUARGA ISLAM - Fata, Nariya (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2017)
According to social studies not all contacts and social relations that occur are religious